Cyclic and constant hyperoxia cause inflammation, apoptosis and cell death in human umbilical vein endothelial cells. Issue 4 (22nd October 2015) - Wu, J.; Hafner, C.; Schramel, J. P.; Kaun, C.; Krychtiuk, K. A.; Wojta, J.; Boehme, S.; Ullrich, R.; Tretter, E. V.; Markstaller, K.; Klein, K. U.
Abstract : Background: Perioperative high‐dose oxygen (O2 ) exposure can cause hyperoxia. While the effect of constant hyperoxia on the vascular endothelium has been investigated to some extent, the impact of cyclic hyperoxia largely remains unknown. We hypothesized that cyclic hyperoxia would induce more injury than constant hyperoxia to human umbilical vein endothelial cells (HUVECs). Methods: HUVECs were exposed to cyclic hyperoxia (5–95% O2 ) or constant hyperoxia (95% O2 ), normoxia (21% O2 ), and hypoxia (5% O2 ). Cell growth, viability (Annexin V/propidium iodide and 3‐(4, 5‐dimethythiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide, MTT) lactate dehydrogenase (LDH), release, cytokine (interleukin, IL and macrophage migration inhibitory factor, MIF) release, total antioxidant capacity (TAC), and superoxide dismutase activity (SOD) of cell lysate were assessed at baseline and 8, 24, and 72 h. A signal transduction pathway finder array for gene expression analysis was performed after 8 h. Results: Constant and cyclic hyperoxia‐induced gradually detrimental effects on HUVECs. After 72 h, constant or cyclic hyperoxia exposure induced change in cytotoxic (LDH +12%, P = 0.026; apoptosis +121/61%, P < 0.01; alive cells −15%, P < 0.01 ; MTT −16/15%, P < 0.01), inflammatory (IL‐6 +142/190%, P < 0.01; IL‐8 +72/43%, P < 0.01; MIF +147/93%, P < 0.01), or redox‐sensitive (SOD +278%, TAC‐25% P < 0.01) markers. Gene expression analysis revealed that constant and cyclic hyperoxia exposure differently activates oxidative stress, nuclear factor kappa B, Notch, and peroxisome proliferator‐activated receptor pathways. Conclusions: Extreme hyperoxia exposure induces inflammation, apoptosis and cell death in HUVECs. Although our findings cannot be transferred to clinical settings, results suggest that hyperoxia exposure may cause vascular injury that could play a role in determining perioperative outcome.